Influence of SERPINA1 Gene Polymorphisms on Anemia and Chronic Obstructive Pulmonary Disease - Sangeetha, Thangavelu; Nargis Begum, Tajuddin; Balamuralikrishnan, Balasubramanian; Arun, Meyyazhagan; Rengasamy, Kannan R. R.; Senthilkumar, Natchiappan; Velayuthaprabhu, Shanmugam; Saradhadevi, Muthukrishnan; Sampathkumar, Palanisamy; Vijaya Anand, Arumugam (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Background. Anemia is one of the predominant hematological conditions, whereas chronic obstructive pulmonary disease (COPD) is a predominant respiratory disease. These two diseases were found to be interlinked, but the physiological pathways are still unclear. Aim. The current study has been aimed at analysing the genetic interrelationship between anemia and COPD in accordance with different altitudes. Methodology. The genetic analysis was performed in the SERPINA1 gene of anemia, COPD, and healthy individuals for the analysis of single nucleotide polymorphism at rs28949274 and rs17580 locations. Result and Discussion. The single nucleotide polymorphism at the locations rs28949274 and rs17580 was present in both anemic and COPD patients. The COPD patients were more prone to mutations (63% had rs28949274, and 11% had rs17580 polymorphisms) than the anemic patients (40% had rs28949274, and 1% had rs17580 polymorphisms). On the basis of altitude, high-altitude individuals were found to be more susceptible to both the polymorphisms. Conclusion. Based on the current findings, we suggest that the SERPINA1 gene has a positive correlation with anemia as well as COPD, and the increase in altitude also influences the diseased conditions in a positive manner.